Kebijakan Manajemen Bencana Berkelanjutan: Pendekatan Terpadu untuk Mitigasi dan Adaptasi Bencana - Yulianti, Neng Cahya; Saepuddin, Eli Apud; Putri, Rossa Amelia; Muhamad , Tamimi; Solehatunnisa, Firlyn; Madina, Listia Ulya (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
Disasters are complex phenomena that significantly affect social, economic and environmental order. The dynamics of climate change, population growth and ecosystem transformation have increased the frequency and intensity of disasters in various parts of the world. This condition demands the development of a comprehensive approach to disaster management that is not merely reactive, but proactive and sustainable. This research examines a comprehensive approach to sustainable disaster management, focusing on integrative mitigation and adaptation strategies. The aim is to analyze a disaster management policy model that is able to create community resilience through a systemic and sustainable approach. The research methodology uses mixed methods by combining qualitative and quantitative approaches through literature studies, policy analysis, and field research in disaster-prone areas. The research conceptual framework is based on the four main dimensions of disaster management: prevention, preparedness, response and post-disaster recovery. The analysis focused on identifying critical factors that affect the effectiveness of disaster management at various levels. The findings confirm that sustainable disaster management requires a proactive approach, not just a reactive response. Mitigation strategies should be locality risk-based and consider the complexity of social-ecological dynamics. The theoretical implications of the research contribute to the development of a new paradigm of disaster management that is holistic, integrative and sustainable. A systemic approach is key in building community resilience. The originality of the research lies in the comprehensive approach that views disaster management as a dynamic system that requires continuous adaptation.